The Effect of Job Satisfaction on Employee Turnover Intention: Case Study in Tanadewa Resort and Spa Ubud - I Putu Very Ferrari; I Gusti Gede Anggareksa Putra Mulyawan; I Gusti Agung Gede Witarsana; Putu Gde Arie Yudhistira (JURNAL BISNIS HOSPITALITI, 2021)
Employee turnover can cause problems within hospitality business. Job satisfaction commonly influence employee turnover intention. Tanadewa Resort and Spa, Ubud has high annual turnover rate. This research’s objective is to analyze the impact of job satisfaction on employee turnover in Tanadewa, Ubud. This research has total population of 48 respondents. Open question is also used to collect qualitative data within the questionnaire. The research uses Simple Linear Regression as analysis method. The result shows job satisfaction has a negative effect to employee turnover intention for 83,7%. The research recommends Tanadewa, Ubud to consider increasing the salary in term of service payment and increase the promotion opportunities.